(untitled) - Win, U Khin (Manila, Philippines, 1991)
This book is a comprehensive treatment of all important factors that influenced Burma’s rice production growth. Author has analyzed patterns of rice production in Burma over the last 100 years, identifying the forces that generated its production growth, and how this has affected the lives of the Burmese population. Author also suggests technological approaches to trigger a second wave of development.
Keywords: Rice,Rice; History.,Research,History; Burma,Burma